Effects of tannic acid on the physical stability, interfacial properties, and protein/lipid co-oxidation characteristics of oil body emulsions. (February 2023) - Liao, Yi; Sun, Yufan; Peng, Xinhui; Qi, Baokun; Li, Yang
Abstract: Herein, we investigated the effects of tannic acid (TA) concentration (0.02–0.70 mg/mL) on the physical stability, interfacial properties, and lipid/protein co-oxidation behavior of oil body (OB) emulsions. The results suggest that the lowest average particle size (0.416 μm), highest absolute ζ-potential (34.03 mV), and best anti-aggregation properties were obtained at a TA concentration of 0.10 mg/mL. Fourier transform infrared spectroscopic analysis showed that TA engaged in hydrogen bonding and hydrophobic interactions with OB proteins, while interfacial property analysis revealed that the influence of TA on OB interfacial proteins was complex and indicated the occurrence of synergistic and competitive interfacial adsorption. At low concentrations (0.02–0.30 mg/mL), TA competed with OB interfacial proteins for adsorption sites, whereas at high concentrations (0.50 and 0.70 mg/mL), it engaged in noncovalent interactions with these proteins to increase the thickness of the OB interfacial layer and thus strengthen the physical barrier responsible for oxidative resistance. Notably, TA increased the oxidative stability of OBs during storage regardless of its concentration, which was related to the capture of TA by the OB interface. Thus, this study explains the action mechanism of TA and OB proteins, provides insights into the co-oxidation of OB lipids and proteins, and deepens our understanding of the oxidation of natural food emulsions. Graphical abstract: Image 1 Highlights: Tannic acid (TA) interacted with oil body (OB) proteins by noncovalent force. TA at low concentration would compete with OB interfacial protein. TA exhibited competitive and synergistic adsorption with OB interfacial protein. TA inhibited the co-oxidation of the OB surface proteins and lipids.